2020
DOI: 10.1002/adbi.202000118
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐Free Synthesis of Dopamine and Serotonin in Two Steps with Purified Enzymes

Abstract: For example, the intermediates of the synthesis of dopamine and serotonin are L-DOPA (L-dihydroxy-phenylalanine) and 5-HTP (5-hydroxytryptophan), respectively, and have found use as administered precursors that are capable of crossing the blood-brain barrier. Although several studies have focused on the characterization of the separate enzymes involved in the biosynthesis of serotonin and dopamine, [3-5] surprisingly little effort has been put into developing enzymatic methods for the production of the final n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 23 publications
2
10
0
Order By: Relevance
“…However, 5-HT was released within 4 h by HaDDC with 5-HTP as a substrate. These results showed that HaDDC exhibited strict substrate speci city similar to that displayed by drDDC from D. melanogaster [7,15]. According to the results shown in Table 1, HaDDC exhibited a high e ciency on 5-HTP, and the conversion rate was 88.45% at 4 h, which was higher than that of TDC reported previously [6,11].…”
Section: Construction Of Chassis Cells For 5-htp Productionsupporting
confidence: 48%
See 2 more Smart Citations
“…However, 5-HT was released within 4 h by HaDDC with 5-HTP as a substrate. These results showed that HaDDC exhibited strict substrate speci city similar to that displayed by drDDC from D. melanogaster [7,15]. According to the results shown in Table 1, HaDDC exhibited a high e ciency on 5-HTP, and the conversion rate was 88.45% at 4 h, which was higher than that of TDC reported previously [6,11].…”
Section: Construction Of Chassis Cells For 5-htp Productionsupporting
confidence: 48%
“…The in vitro cascade of SmTPH and HaDDC was conducted in a reaction system (2 mL) that contained 7 mM DTT, 0.1 M ferrous ammonium sulfate, 0.1 mg/mL catalase, 0.6 mM BH 4 , 0.1 mM PLP, 0.5 mM L-Trp, 100 µL puri ed SmTPH (1.0 g/L), 100 µL puri ed HaDDC (1.0 g/L) and 50 mM HEPES (pH 7.0), and incubated at 30℃ [1,7]. In addition to these cofactors, reactions were supplemented with catalase and dithiothreitol to protect against oxidative degradation [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, previous study reported that DDC can catalyse 5-HTP into 5-HT without the ability of converting l-Trp [13,14]. However, almost studies have focused on the characterization of the enzyme involved in the biosynthesis of dopamine, and systematic studies for the production of 5-HT have not been conducted [7,15].…”
Section: Open Accessmentioning
confidence: 99%
“…Currently, the main supply of 5-HT depends on the extraction from mammals (e.g. buffalo, rat, and pig) or plants (safflower, sea buckthorn, and Moringa Oleifera seeds) [7]. However, the low 5-HT yield from natural extraction and the insufficient supply of raw materials…”
Section: Introductionmentioning
confidence: 99%